Does Foot Position and Local of Measurement Influence on Ankle Medial Clear Space? - Tiago Baumfeld MD; Daniel Baumfeld MD; João Cangussú MD; Benjamim Macedo MD; Thiago Silva; Fernando Raduan MD; Caio Nery MD (Foot & Ankle Orthopaedics, 2017)
Category: Ankle, Sports, Trauma Introduction/Purpose: The ankle Medial Clear Space (MCS) is frequently used in foot and ankle surgery for determining the competence of the deltoid ligament in Weber B ankle fractures. A widened MCS indicates deltoid ligament incompetence, requiring surgery to prevent lateral talar shift. Controversy still exists regarding Medial Clear Space (MCS) normal and abnormal values, and its possible variation in previously uncontrolled biases. Sex, height, foot position, and type of radiograph were all described as possible influencing factors. The objective of this study was to access how much different degrees of plantar flexion, all performed with and without stress, influence on MCS width. Methods: We submitted 30 volunteers to six different anteroposterior non-weight bearing digital radiographs of the ankle in the following positions: neutral, neutral with external rotation stress, physiologic plantar flexion (FPF), physiologic plantar flexion with external rotation stress, maximum plantar flexion (MPF) and maximum plantar flexion with external rotation stress. The medial clear space MCS oblique (MCSo) and perpendicular (MCSp) were measured in all images by an experienced foot and ankle surgeon. Results: The data analysis showed with statically significance that the position of the foot does influence in the value of both MCSp and MCSo (p<0,05), regardless of three exceptions. MCSo does not change statistically between FPF with stress and MPF with stress. On the other hand, MCSp did not change in two situations: between FPF and Neutral with stress and between MPF and FPF with stress. It is noteworthy that MCSo, on average, was 15% wider than MCSp in all positions tested. It is also noticeable that, from the neutral position, plantar flexing the ankle has a great impact on MCS than external rotation stress, increasing MCSp by 25% and 22% respectively. MCSo follows the same pattern, with 21% and 17% respectively. Conclusion: This study is unique on showing that many different ways of positioning the foot and making stress radiographs do result in completely different MCS values, and that these values differ depending on the anatomical site they are measured. All these data indicates that we need to establish a gold standard for measuring MCS, taking into account patient sex, height, local of measurement of MCS, position of the foot and type of radiograph (AP or Mortise). This study was not able to address all variables that influence directly on MCS and therefore did not intended to establish this new gold standard.